ANALISIS PENGARUH RELIGIUSITAS, LABEL HALAL DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH DI TOKO CANDRA SEMARANG - Adhitya Yoga Prasetya; Ernah Ernah; Dhian Andanarini M S (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
The reason for this study is to examine the impact of the religiosity, halal name and word of mouth on purchasing decisions. Religiosity, Halal Label, Word of Mouth, and Purchase Decision are the dependent variables analyzed in this study. The example utilized in this study comprised of 100 clients of Wardah restorative items. Through the distribution of questionnaires, the purposive sampling method was used for sampling. Validity and reliability tests, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, model feasibility tests (F tests), individual parameter significance tests (t statistic tests), and coefficient tests were utilized in this study's data analysis. determination (R2) using the SPSS software. Word of mouth had a positive and significant impact on purchasing decisions, and religiosity had a positive and significant impact. Halal Label had a positive and significant effect.